PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA BORNEO INDOOR FUTSAL BANJARMASIN - Melsandi; Dwi Wahyu Artiningsih; Mardah, Siti; Firdaus, Firdaus (Jurnal Manajemen & Bisnis Jayakarta, 2024)
This research was conducted to determine the magnitude of the influence of leadership style and motivation on employee performance at Borneo Indoor Futsal Banjarmasin. This type of research is quantitative descriptive. The population used is all employees from this research site. The sample used was 30 people. Data was obtained through distributing questionnaires to all respondents. This research was analyzed using the IBM version of the SPSS 25 software test tool. The analysis tests carried out were instrument tests, classist assumption tests, multiple linear regression tests, T tests, F tests and termination coefficient tests. From the research results it was found that the data used were valid and reliable. For the partial influence of leadership style and motivation on employee performance positive and significant effect. Likewise, the F test results show that the two independent variables have a positive and significant effect on the dependent variable together.